Islamic Religious Education Learning Process Through the Utilization of ChatGPT - Mulya, Berlian Dwi Puji; Nasikhin; Fihris; Junaedi, Mahfud (Yayasan Letiges Konsultan Sosial, 2025)
This study aims to analyze the views of Islamic Education students on the use of ChatGPT in learning and review the Islamic perspective on the use of ChatGPT in the context of education. The approach used is qualitative with a case study method. Data were collected through a Google Forms survey, semi-structured interviews, and observations. Data validity with source triangulation techniques ensures information accuracy from various sources. Data analysis was carried out using the Miles and Huberman interactive approach, which includes data reduction, data presentation, and conclusion. The study results indicate that ChatGPT plays an essential role in supporting student learning, and it is used mainly to access information needed in every learning process of Islamic Education students, solve problems, and provide relevant answers to academic needs. From an Islamic perspective, students realize the importance of using ChatGPT wisely, referring to verses of the Qur'an such as QS. Al-Alaq verse 1 and QS. Az-Zumar verse 9 emphasizes good intentions in seeking knowledge and ensuring the truth of information. This finding strengthens the idea that the use of ChatGPT must pay attention to aspects of academic ethics taught by Islam. This research enriches the literature on technology integration in religious education, especially regarding using ChatGPT with an approach based on Islamic values.